Implementation of a Neurogenic Bowel Program for Spinal Cord Injury in the Acute Care Setting: Perceptions of Patients and Staff. Issue 3 (3rd July 2019) - Borsh, Sarah; Sikka, Seema; Callender, Librada; Bennett, Monica; Reynolds, Megan; Driver, Simon
Abstract: A prospect cohort and case-control was employed to (1) establish a neurogenic bowel (NB) program after spinal cord injury (SCI) in the acute care setting; (2) examine clinician knowledge ability to deliver the NB program; and (3) evaluate patient knowledge, satisfaction, and quality of life. Educational in-service describing NB clinical practice guidelines (CPGs) and order set was delivered to staff followed by a pre-/post-education, 3- and 12-month survey. The patient intervention followed 24 patients with NB to evaluate the program and compared to 28 retrospective case-control patients followed by a pre-/post-intervention survey to measure knowledge of SCI, NB program and quality of life. Injury information and bowel medication use was compared between cases and controls. Clinician knowledge of NB CPGs improved. There were no significant clinical differences between patient groups. Patient knowledge and satisfaction improved post-intervention. Education to staff and patients is imperative to facilitate a NB program to meet the needs for individuals with SCI.